2022
DOI: 10.3390/ijms232314528
|View full text |Cite
|
Sign up to set email alerts
|

The Black Box of Cellular and Molecular Events of Plasmodium vivax Merozoite Invasion into Reticulocytes

Abstract: Plasmodium vivax is the most widely distributed malaria parasite affecting humans worldwide, causing ~5 million cases yearly. Despite the disease’s extensive burden, there are gaps in the knowledge of the pathophysiological mechanisms by which P. vivax invades reticulocytes. In contrast, this crucial step is better understood for P. falciparum, the less widely distributed but more often fatal malaria parasite. This discrepancy is due to the difficulty of studying P. vivax’s exclusive invasion of reticulocytes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…Second, it can be used for the development of bioreceptors such monoclonal antibodies and aptamers for the diagnosis of P. vivax -specific malaria [ 32 , 55 ]. As mentioned above, since the life cycle of P. vivax in the human host is different that of P. falciparum [ 13 , 14 , 15 , 16 , 17 , 18 ], the parasite must be distinguished. Finally, it can be used as a useful tool for basic research related to identification of the metabolic pathway of parasites involved in PvLDH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, it can be used for the development of bioreceptors such monoclonal antibodies and aptamers for the diagnosis of P. vivax -specific malaria [ 32 , 55 ]. As mentioned above, since the life cycle of P. vivax in the human host is different that of P. falciparum [ 13 , 14 , 15 , 16 , 17 , 18 ], the parasite must be distinguished. Finally, it can be used as a useful tool for basic research related to identification of the metabolic pathway of parasites involved in PvLDH.…”
Section: Resultsmentioning
confidence: 99%
“…P. vivax forms a hypnozoite (dormant form) in the liver, which unless completely eliminated, can get re-activated and cause recurrence of malarial infection [ 9 , 10 , 11 , 12 , 13 ]. In addition, recent studies have revealed that P. vivax evades the host immune system [ 14 ], is fatal to infants and children [ 15 ], and invades the reticulocytes (called young red blood cells) [ 16 , 17 , 18 ]. Therefore, measures for eliminating P. vivax are completely warranted.…”
Section: Introductionmentioning
confidence: 99%
“…With its unique biology, such as early inducement of gametocytes, restriction of invading reticulocytes, which causes low parasitemia that challenges clinical and paraclinical detection, and the ability to trigger hypnozoiteinduced relapses, P. vivax constitutes a key target in the last global battle against malaria (Adams and Mueller, 2017;Bantuchai et al, 2022;Moreno et al, 2022). Although the involvement of some P. vivax-expressed proteins, such as P. vivax Duffy binding protein (PvDBP) (Kar and Sinha, 2022), and most recently P. vivax reticulocyte-binding protein 1a and 1b (PvRBP1a and 1b) (Han et al, 2016), 2a (PvRBP2a) (Malleret et al, 2021), and 2b (PvRBP2b) (Gruszczyk et al, 2018) in reticulocyte invasion are well documented, the mechanism underlying this process remains largely unknown (Molina-Franky et al, 2022). The recent increase in human malaria cases due to a zoonotic malaria parasite, P. knowlesi, with the highest prevalence in Southeast Asia (Jeyaprakasam et al, 2020), has revealed that the pathogen is able to induce severe, fatal disease.…”
Section: Introductionmentioning
confidence: 99%
“…Pv causes significant disease, particularly in low-middle-income countries burdened with poor nutrition, anemia, and co-infections [3]. During the erythrocytic or blood stage, Pv merozoites infect reticulocytes, primarily at the sites of erythropoiesis in the bone marrow and spleen [4][5][6]. Pv forms a dormant pre-erythrocytic or liver phase (hypnozoites), causing frequent relapses, further contributing to anemia and other complications [7,8].…”
Section: Introductionmentioning
confidence: 99%